2022
DOI: 10.1021/jacs.2c10823
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-Enhanced Electrocatalysis of Sustainable Oxygen Evolution Using Organoselenium Functionalized Metal–Organic Nanosheets

Abstract: Remolding the reactivity of metal active sites is critical to facilitate renewable electricity-powered water electrolysis. Doping heteroatoms, such as Se, into a metal crystal lattice has been considered an effective approach, yet usually suffers from loss of functional heteroatoms during harsh electrocatalytic conditions, thus leading to the gradual inactivation of the catalysts. Here, we report a new heteroatom-containing molecule-enhanced strategy toward sustainable oxygen evolution improvement. An organose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…[36][37][38] The wavelet transform (WT) was further conducted to reveal the EXAFS oscillations for Co K-edge. In the WT analysis, the CoÀ Co DASs/ZCC also showed the obvious intensity feature assigned to CoÀ O bonds, which was consistent with reference Co 3 O 4 , [39,40] further revealing the existence of Co 3 O 4 species in catalysts (Figure 2d-f). The above XAFS fitting results also found that the slightly elongated CoÀ O bonds (1.95 Å) of CoÀ Co DASs/ZCC with longer interatomic distance owing to the formation of SÀ CoÀ O HGBIs (Figure 2g), compared with bulk Co 3 O 4 (1.91 Å).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…[36][37][38] The wavelet transform (WT) was further conducted to reveal the EXAFS oscillations for Co K-edge. In the WT analysis, the CoÀ Co DASs/ZCC also showed the obvious intensity feature assigned to CoÀ O bonds, which was consistent with reference Co 3 O 4 , [39,40] further revealing the existence of Co 3 O 4 species in catalysts (Figure 2d-f). The above XAFS fitting results also found that the slightly elongated CoÀ O bonds (1.95 Å) of CoÀ Co DASs/ZCC with longer interatomic distance owing to the formation of SÀ CoÀ O HGBIs (Figure 2g), compared with bulk Co 3 O 4 (1.91 Å).…”
Section: Resultssupporting
confidence: 79%
“…The above XAFS fitting results also found that the slightly elongated CoÀ O bonds (1.95 Å) of CoÀ Co DASs/ZCC with longer interatomic distance owing to the formation of SÀ CoÀ O HGBIs (Figure 2g), compared with bulk Co 3 O 4 (1.91 Å). [36,39] The relatively elongated distance was also very beneficial to enhance the stability. [35] Furthermore, the symmetric dual Co sites with appropriate atomic distances ( � 2.80 Å) were beneficial to facilitating OÀ O radical coupling for two active site OER process under…”
Section: Resultsmentioning
confidence: 99%
“…), their widespread application is restricted, requiring the development of other electrocatalysts free of noble metals, such as transition-metal oxides or hydroxides. 5 Transition-metal-based oxides, chalcogenides, 6–8 hydroxides, phosphides, double perovskites, metal–organic frameworks (MOFs) 9,10 and their composites with carbon (graphene, carbon nanotubes, etc. ) have been developed through extensive scientific investigations.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] A common feature of all these systems is that the cathode region undergoes a reduction reaction while the anode region experiences an oxygen evolution reaction (OER). [6][7][8][9][10] However, the sluggish and multi-step proton-coupled electron transfer process of the OER plays a decisive role, especially in electrocatalytic water-splitting systems. [11][12][13][14][15][16] Water splitting is considered a straightforward, environmentally friendly, and cost-effective approach to hydrogen production instead of hydrocarbon reforming or cracking.…”
Section: Introductionmentioning
confidence: 99%
“…1–5 A common feature of all these systems is that the cathode region undergoes a reduction reaction while the anode region experiences an oxygen evolution reaction (OER). 6–10…”
Section: Introductionmentioning
confidence: 99%